22.4k views
3 votes

4 √(40) + 7 √(160)


User Theknut
by
4.9k points

2 Answers

4 votes

Answer:

36
√(10)

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Simplifying the radicals in the expression


√(40)

=
√(4(10))

=
√(4) ×
√(10) = 2
√(10)


√(160)

=
√(16(10))

=
√(16) ×
√(10) = 4
√(10)

Thus

4
√(40) + 7
√(160)

= 4 × 2
√(10) + 7 × 4
√(10)

= 8
√(10) + 28
√(10)

= 36
√(10)

User John Kitonyo
by
4.7k points
3 votes

Answer:

Explanation:

4
4√(40) + 7 √(160) = 4√(2*2*2*5)  + 7√(4*4*5*2)\\  = 4*2√(10)  + 7*4√(10)\\ = 8√(10) + 28√(10) \\

= (8 + 28)√10

= 36√10

User Jordumus
by
5.1k points